2002
DOI: 10.1017/s0022112001006577
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the 1954 suspension experiments of R. A. Bagnold

Abstract: In 1954 R. A. Bagnold published his seminal findings on the rheological properties of a liquid-solid suspension. Although this work has been cited extensively over the last fifty years, there has not been a critical review of the experiments. The purpose of this study is to examine the work and to suggest an alternative reason for the experimental findings. The concentric cylinder rheometer was designed to measure simultaneously the shear and normal forces for a wide range of solid concentrations, fluid viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 37 publications
2
83
0
Order By: Relevance
“…This equilibration of σ e to an imposedγ and m is tantamount to development of steady dispersive normal stress in the enclosed shear cell experiments of Bagnold [80] (cf. [81,82]). On the other hand, if a steadily shearing grainfluid mixture freely dilates or contracts when a step change in σ e is externally imposed, then (3.17) implies thatγ subsequently equilibrates to a new steady state as dm/dt → 0 and ψ → 0.…”
Section: (D) Definition Of Dilation Ratementioning
confidence: 99%
“…This equilibration of σ e to an imposedγ and m is tantamount to development of steady dispersive normal stress in the enclosed shear cell experiments of Bagnold [80] (cf. [81,82]). On the other hand, if a steadily shearing grainfluid mixture freely dilates or contracts when a step change in σ e is externally imposed, then (3.17) implies thatγ subsequently equilibrates to a new steady state as dm/dt → 0 and ψ → 0.…”
Section: (D) Definition Of Dilation Ratementioning
confidence: 99%
“…13,14 At low Reynolds number, the viscosity can suppress this radial motion, but, as the Reynolds number increases, secondary flows, often referred to as Taylor vortices, may change the character of the flow field from a simple shear flow; this change in flow character can affect the measurement of the stresses. A detailed analysis by Hunt et al 15 demonstrated that Bagnold's experimental results were marred by the presence of secondary flows that developed at the boundaries of the rheometric device. By accounting for the contribution of the vortices to the shear stress, Hunt et al demonstrated that Bagnold's linear to quadratic transition could be explained by assuming a laminar Newtonian flow with an effective viscosity that depended on the solid concentration.…”
Section: -mentioning
confidence: 99%
“…Bagnold's original 1954 work [Hunt et al, 2002]. An alternative to the inertial regime is the elastic regime, which is characterized as ''granular materials under dense conditions where particles are in persistent contact with their neighbors and the elasticity of the material becomes an important rheological parameter'' [Campbell, 2002, p. 261].…”
Section: Discussionmentioning
confidence: 99%